1998
DOI: 10.4319/lo.1998.43.7.1746
|View full text |Cite
|
Sign up to set email alerts
|

Annual average abundance of heterotrophic bacteria and Synechococcus in surface ocean waters

Abstract: Global abundance of marine bacteria was investigated at the annual climatological scale. In surface waters of diverse marine habitats, the annual average abundances of heterotrophic bacteria and the photosynthetic cyanobacterium Synechococcus are directly related to annual average temperature below 14°C. Notably, average nitrate concentrations at the surface are never high where the temperature is above 14°C. These results suggest that, over the course of a year, temperature is the dominant factor affecting ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
152
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(176 citation statements)
references
References 64 publications
19
152
1
4
Order By: Relevance
“…However, salps process much higher fluid volumes than crustaceans, due to the considerably larger cross-sections of their feeding currents. (23), bacteria (24,25), Prochlorococcus (26), Synechococcus (25), nanoplankton (24,27), and microplankton (24,27). Line is regression of microphytoplankton concentration vs. cell diameter, log 10 C = −0.91 log 10 (d P 3 π/6) + 3.5; C (particles·mL −1 ), d P (μm) (28).…”
Section: Resultsmentioning
confidence: 99%
“…However, salps process much higher fluid volumes than crustaceans, due to the considerably larger cross-sections of their feeding currents. (23), bacteria (24,25), Prochlorococcus (26), Synechococcus (25), nanoplankton (24,27), and microplankton (24,27). Line is regression of microphytoplankton concentration vs. cell diameter, log 10 C = −0.91 log 10 (d P 3 π/6) + 3.5; C (particles·mL −1 ), d P (μm) (28).…”
Section: Resultsmentioning
confidence: 99%
“…In the North Atlantic Ocean (40ºN, 23ºW) during spring, Veldhuis et al (2001) also reported that cell viabilities of Synechococcus ranged from 75 to 90%, using the SYTOX Green membrane permeability assay. It is known that temperature is the dominant factor controlling the growth and loss of Synechococcus in colder waters (Li, 1998). Moreover, Agustí and Sánchez (2002) In contrast to Synechococcus spp., the cell viabilities of eukaryotic ultraphytoplankton (<10 µm in size) were relatively low (from 26 to 41%) at all stations in September 2003 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal and monthly patterns of variation have been observed using molecular methods at multiple aquatic time-series sites, which suggest that environmental change elicits a biological response; many, but not all, have also shown recurrence (Acinas et al, 1997;Li, 1998;Morris et al, 2005;Fuhrman et al, 2006;Alonso Sáez et al, 2007;Kan et al, 2007;Treusch et al, 2009;Campbell et al, 2011;Eiler et al, 2011;Gilbert et al, 2012;Robidart et al, 2012). For example, seasonality in Synechococcus ecotypes was observed in the Southern California Bight, primarily for clades I and IV (Tai and Palenik, 2009), and in the Chesapeake Bay (Cai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%